Development of hot melt ethylene vinyl acetate (EVA) adhesive for packaging industry - Mohd Syahmi Hafizi, Ghani (2015)
Hot-melt adhesives have been commercially available for a long time and they are used in a wide range of applications. In recent years, packaging industry prefers to use hot melt adhesive based on polyolefin because polyolefin provide ease of processing, low off-taste, low smell and heat seal ability. In this research, it is intended to develop the formulation for Ethylene Vinyl Acetate (EVA) based hot melt adhesive with the same properties of polyolefin based hot melt adhesive since EVA offers low cost than polyolefin. To develop new formulation of EVA hot melt adhesive (HMA), EVA copolymers with various melt index were blended together with resin, wax and antioxidant in the molten state. The performance of new formulations was compared with commercial polyolefin hot melt adhesive. Three formulations of EVA hot melt adhesive have been developed. The thermal properties such as glass transition temperature and melt viscosity were studied by using differential scanning calorimeter (DSC) and Brookfield Viscometer. From DSC curve, the result indicated that three new formulations and commercial polyolefin has a glass transition temperature between -20 0C and -25 0C. Implying, the EVA copolymer blend with resin is compatible. The peak observed on the heating curve corresponded to the melting point, Tm. EVA-HMA 1 and EVA-HMA 3 is comparable with commercial polyoelfin based on identical broad peak. The melt viscosity of all EVA HMA formulation and commercial polyolefin HMA decrease with increasing the temperature. Hot melt adhesive with lower viscosity will have more flexibility to flow out, indicating that it has better wetting properties when applied to the substrate. EVA-HMA 3 have the best performance to be made the hot melt adhesive for the packaging industry because of comparable thermal properties and viscosity at desired temperature with commercial polyolefin adhesive. Further research needs to be conducted on EVA-HMA 3 for other properties to confirm its viability in replacing the commercial polyolefin based hot melt adhesive in packaging industry.